Response of juvenile Chinook salmon to managed flow: lessons learned from a population at the southern extent of their range in North America. (26th February 2014) - Zeug, S. C.; Sellheim, K.; Watry, C.; Wikert, J. D.; Merz, J.
Abstract Fourteen years (1996–2009) of juvenile Chinook salmon, Oncorhynchus tschawytscha (Walbaum), migration data on the regulated Stanislaus River, California, USA were used to evaluate how survival, migration strategy and fish size respond to flow regime, temperature and spawner density. An information theoretic approach was used to select the best approximating models for each of four demographic metrics. Greater cumulative discharge and variance in discharge during the migration period resulted in higher survival indices and a larger proportion of juveniles migrating as pre‐smolts. The size of pre‐smolt migrants was positively associated with spawner density, whereas smolt migrant size was negatively associated with temperature and positively associated with discharge. Monte Carlo techniques indicated high certainty in relationships between flow and survival, but relationships with juvenile size were less certain and additional research is needed to elucidate causal relationships. Flow is an integral part of the habitat template many aquatic species are adapted to, and mismatches between flow and life history traits can reduce the success of migration and the diversity of migratory life history strategies. The analyses presented here can be used to assist in the development of flow schedules to support the persistence of salmon in the Stanislaus River and provide implications for populations in other regulated rivers with limited and variable water supply.